Corpus testimonial: recopilación y preservación de memorias colectivas del centro de detención y tortura «venda sexy» - Ortúzar Tornero, María Fernanda (2024)
The «Venda Sexy» Detention and Torture Center was a barrack rented by the Dirección de Inteligencia Nacional (DINA) that exerted political and sexual violence as a punishment pattern for those who fought against Augusto Pinochet’s dictatorship in Chile. After the transition to democracy, the women that were political prisoners were represented as victims and also witnessed the difficulty behind recognizing political and sexual violence as a repressive method imbued by gender components. Their experiences were collected in committees that kept them in a private sphere and the enclosure where they were subjected is still private property, because the state has not retrieved it. As a consequence of the deprivation of a memory site that exhibits what happened at «Venda Sexy», the survivors assumed an activism role occupying the Irán and Los Plátanos street corner, in Macul, to commemorate and protest. Nevertheless, they’ve faced the destruction of their memorials and the interruption of their activities, along with being intimidated for interfering in that place. In this scenario, the present design investigation intertwines the collective memories of those who were political prisoners at «Venda Sexy» proposing the reconstruction of historical memory grounded from orality, administrating tools to speculate around a site that belongs to them, but where they cannot burst into. Applying participative design, that democratizes the process by incorporating those who are involved in the project, and prototyping, to cope with the project’s intangible dimension, enables a medium to narrate what exceeds the institutional threshold. The project is in a development phase that will lead to a digital memory site that acts as an accessible showcase for the situated narratives that were collected.